Análise do comportamento não linear geométrico e físico de pórticos planos de concreto armado - Telles, José Claudio de Faria (1976)
This work is a further step into a more theoretical and profound study on reinforced concrete structures. A program is presented for analysis of reinforced concrete plane frames, where two different types of non linearities are dealt with: 1) Geometrical non linearity: considering the second-order effects, resulting from axial-flexural interaction; 2) Physical non linearity: considering the physical characteristics of materials (concrete and steel), through the approach adopted by the CEB-FIP recommendations. This program was developed for straight members, with any cross-section (symmetrical to the structure plane), and with any reinforcement distributions. As for its applicability, it may be employed for an analysis of forces and displacements for a definite loading, as well as for a research on load-bearing capacity, in which its non linear performance is analysed for each loading intensity, until the structure maximum load-bearing capacity is obtained. At the end of this study, a few examples and comparisons with other approaches of the sort are included, as well as some remarks on the effects of creep in concrete under sustained loads.